2009
DOI: 10.1680/macr.2008.00049
|View full text |Cite
|
Sign up to set email alerts
|

A model for predicting thermal conductivity of concrete

Abstract: This study investigates the thermal conductivity of fly ash concrete. Experiments were conducted to obtain the thermal conductivity of fly ash-cement pastes and mortars. Pastes were prepared to investigate the effect of fly ash, and mortar specimens were prepared for studying the effect of aggregates. It was found from the test that the replacement of cement by fly ash resulted in lower thermal conductivity. Thermal conductivity of mortar was higher than that of the cement paste. A simple parallel model for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 11 publications
3
12
0
Order By: Relevance
“…The results of this study, showed in Fig. 8, verified with result of Choktaweekarn [1]. For the controlled specimens of both mixture, the obtained results clearly showed that due to the low specific heat of water to binder ration w/b=0.4, its temperature increased proportionally higher than that of water to binder ration w/b=0.6.…”
Section: Effect Of Water To Binder Ratio On Changing Of Concrete Tempsupporting
confidence: 85%
See 4 more Smart Citations
“…The results of this study, showed in Fig. 8, verified with result of Choktaweekarn [1]. For the controlled specimens of both mixture, the obtained results clearly showed that due to the low specific heat of water to binder ration w/b=0.4, its temperature increased proportionally higher than that of water to binder ration w/b=0.6.…”
Section: Effect Of Water To Binder Ratio On Changing Of Concrete Tempsupporting
confidence: 85%
“…A proposed model to predicted the specific of concrete by Choktaweekarn [1] clarified that the water to binder ratio significantly affects the specific heat of concrete. Specifically, the predicted model estimates that for concrete with water to binder ratio w/b=0.4, its specific heat is approximately 814.75 / .…”
Section: Effect Of Water To Binder Ratio On Changing Of Concrete Tempmentioning
confidence: 99%
See 3 more Smart Citations